Imaging in Heart Failure with Preserved Ejection Fraction: A Multimodality Imaging Point of View - Serkan Ünlü; Özge Özden; Ahmet Çelik (Cardiac Failure Review)
Heart failure with preserved ejection fraction (HFpEF) is an important global health problem. Despite increased prevalence due to improved diagnostic options, limited improvement has been achieved in cardiac outcomes. HFpEF is an extremely complex syndrome and multimodality imaging is important for diagnosis, identifying its different phenotypes and determining prognosis. Evaluation of left ventricular filling pressures using echocardiographic diastolic function parameters is the first step of imaging in clinical practice. The role of echocardiography is becoming more popular and with the recent developments in deformation imaging, cardiac MRI is extremely important as it can provide tissue characterisation, identify fibrosis and optimal volume measurements of cardiac chambers. Nuclear imaging methods can also be used in the diagnosis of specific diseases, such as cardiac amyloidosis.